PSXVI-28 Documenting production parameters associated with beef production without mature cows. (7th December 2018) - Harrison, M; Seidel, G; Ahola, J; Rhoades, R; Mooney, D
Abstract: Increasing production costs prompted efforts to improve beef production efficiency. The All Heifer, No Cow (AHNC) production system involves insemination of nulliparous heifers with sexed semen to produce primarily female calves that are early weaned 3 months after parturition. Dams are finished on a high concentrate diet (105 ± 12d) and harvested before 30 months of age. Every animal in the enterprise is growing, which eliminates mature cow maintenance costs and improves efficiency. The objective was to assess AHNC production parameters. In years 1 (n = 53) and 2 (n = 57) Angus-based heifers were purchased and managed under the AHNC system. Female calves started in years 1 and 2, plus purchased replacements, became dams in years 3 (n = 53) and 4 (n = 56), respectively. Pregnancy rate at 30 d post fixed time AI with sexed semen was 46.4 ± 4.8 %, and 92.3 ± 1.1 % were pregnant after a second round of AI and bull exposure. Using AHNC, 67.0 ± 15.8 % of females replaced themselves with a heifer. The remaining 33.0 % were purchased from outside the system. During finishing, ADG was 1.8 ± 0.8 kgd-1 and DMI was 15 ± 3.5 kgd -1 . Dressing percent was 60.0 ± 1.9 %. The USDA quality grading system classified 28.4 % of the carcasses (n = 176) as C-maturity. However, lean maturity (A 00 = 100, B 00 = 200, etc.) and marbling score (slight 00 = 300, small 00 = 400, etc.) for A and B versus C maturity were 165 ± 24 and 165 ± 26 ( P = 0.83) and 456 ± 93 and 456 ± 76 ( P = 0.78), respectively. In conclusion, AHNC produced quality carcasses. Calving at a younger age, starting the finishing phase earlier, and innovative marketing strategies may help reduce incidence of C-maturity carcasses.